Institutionalizing corporate social responsibility (CSR) in Uganda: does it matter? - Nkundabanyanga, Stephen K.; Okwee, Alfred (Social Responsibility Journal, 2011)
The purpose of this study is to establish the relationship between CSR, managerial discretion, competences, learning and efficiency and perceived corporate financial performance in order to establish the legitimacy and value of CSR, taking managers’ perspectives in Uganda. Design/methodology/approach – The study used quantitative, correlation and regression analyses and collected primary data through a structured questionnaire on a sample of 100 firms. Findings – The results indicate that managerial discretion and competences, learning and efficiency are significant predictors of perceived corporate financial performance, but CSR is not. However, the results show serendipitously that managerial discretion’s predictive potential of perceived corporate performance is moderated by CSR. Result limitations/implications – The study focuses on corporate social responsibility, a concept not very well appreciated and only understood as philanthropic and not really viewed as a means for improved financial performance in Uganda. Practical implications – Our study implies that while upholding the ideals of CSR, companies in Uganda need to enhance managerial discretion in their contracting process and develop competences, learning and efficiency in order to impact positively on performance. Originality/value – This study contributes to the dearth of CSR literature on the African experience by examining the perceptions of managers on CSR’s predictive potential of corporate financial performance in Uganda.
Keywords: Corporate social responsibility; Managerial discretion; Competences; Performance; Uganda